Understanding the basis of major depressive disorder in oncological patients: Biological links, clinical management, challenges, and lifestyle medicine - Fraile-Martinez, Oscar; Alvarez-Mon, Miguel A.; Garcia-Montero, Cielo; Pekarek, Leonel; Guijarro, Luis G.; Lahera, Guillermo; Saez, Miguel A.; Monserrat, Jorge; Motogo, Domitila; Quintero, Javier; Alvarez-Mon, Melchor; Ortega, Miguel A. (Frontiers in Oncology, 2022)
During recent years, the incidence and survival of different types of cancer has been rising and hence, its prevalence. The increase in survival in recent years exposes the patient to a set of stressful factors such as more rigorous follow-up, more aggressive therapeutic regimens that, added to the diagnosis of the disease itself, cause an increase in the incidence of depressive disorders. These alterations have important consequences for the patient, reducing their average survival and quality of life and for these reasons, special emphasis has been placed on developing numerous screening tests and early recognition of depressive symptoms. Despite cancer and major depressive disorder are complex and heterogeneous entities, they also share many critical pathophysiological mechanisms, aiding to explain this complex relationship from a biological perspective. Besides, a growing body of evidence is supporting the relevant role of lifestyle habits in the prevention and management of both depression and cancer. Therefore, the present study aims to perform a thorough review of the intricate relationship between depression and cancer, with a special focus on its biological links, clinical management, challenges and the central role of lifestyle medicine as adjunctive and preventive approaches to improve the quality of life of these patients.